The Relevance of SFAS 33 Inflation Accounting Disclosures in the Adjustment of Stock Prices to Inflation. - McDonald, Bill; Morris, Michael H. (The Accounting Review, 1984)
Abstract ABSTRACT: This study tests the reaction of security returns to anticipated and unanticipated inflation using SFAS 33 data to stratify firms cross-sectionally by inflation sensitivity. The cross-sectional stratification allows for the distributive effects of inflation and provides a unique means of assaying the accounting disclosures. The results confirm the significant negative impact of unanticipated inflation on security returns for the 1980-82 period. The market measure of inflation sensitivity, however, does not appear to be related in any way to accounting measures of inflation sensitivity based on SFAS 33 data.